Online buying behavioural intention in indonesia: During new normal protocol - Nur Afifah; Ilzar Daud; Erna Listiana; Hansen Tandra (STIE AMKOP, 2023)
This study was conducted to propose and test a conceptual model in resolving research gaps regarding online buying behavioral intention during the new normal protocol, where age and income level are moderating variables. This study adopts UTAUT2 theory as the basis for resolving research gaps by developing new normal protocol variables and internet self efficacy. Data were collected from 479 respondents in various parts of Indonesia, as samples in the study to test the proposed model, using the structural equation modeling (SEM)-PLS software. The main finding of this study is to show that although the new normal protocol creates a new cultural change in online buying behavior, online buying has become an old culture by consumers in Indonesia even before the Covid-19 pandemic, due to the influence of individual consumers not because of the new normal protocol. Other findings related to the moderation test showed that there was no moderating role of age and income level on the relationship between the new normal protocol and online buying behavior Keywords: Consumer Behavior, Online Purchasing, New Normal Protocol